War Crimes Proceedings Against Members of the Serbian Community in the Territory of the Autonomous Province of Kosovo and Metohija from 1999 to 2023 (Part I) - Grujić, Zdravko V. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
War crimes proceedings in the territory of the AP of Kosovo and Metohija were initiated as early as the end of 1999 and to this day characterize the relationship of the provisional institutions of self-government in the province and, somewhat later, self-proclaimed institutions and various organizational forms of the so-called judicial system towards the Serbian community, both as individuals and as a Serbian national collectivity and identity. Considering that in a large number of cases in these proceedings the nationality of prosecutors and judges was sufficient to predict the outcome of the case, the evidence presented and the judicial “truth” established in various proceedings aimed not only at punishing the accused, but also at intimidating and collectively criminalizing members of the Serbian community who live or have lived on the territory of the Autonomous Province of Kosovo and Metohija.The one-sided and ethnically motivated approach and influence of prosecutors and quasi-judicial bodies that are actually, locally or functionally competent for conducting criminal proceedings for war crimes were, to some extent, reduced in situations where foreign (international) prosecutors and judges were involved in the cases that were being conducted. As expected, the changed ethnic structure within the so-called judicial system led to decisions that denied or downplayed the previously “established” practice of punishing those accused of war crimes (members of the Serbian community).However, although the role of international representatives of UNMIK and EULEX in the work of the so-called judicial bodies in the province can be observed, analyzed, and reviewed from different perspectives, the fact is that in the last few years, when there was a complete transfer of the cases to the so-called specialized judicial bodies in war crimes proceedings, the pressure on individuals accused of committing war crimes or the Serbian collectivity becomes something that could be called institutional ethnic persecution. In the paper, the author points out the different phases of the “creation” of the so-called judicial system competent for war crimes proceedings, and other bodies that are actually responsible for conducting these proceedings for war crimes committed on the territory of the province; the different approach to members of the Serbian community as defendants and victims of war crimes, focusing the analysis on the current situation in which, practically, every member of the Serbian community, if he lives or has a certain right (or property) in the territory of the province, can be considered a “suitable target” for initiating war crimes proceedings
Keywords: war crimes; AP of Kosovo and Metohija; Serbian community